Respons Bunga Matahari (Helianthus annuus L.) akibat Pemberian Dosis NPK dan Waktu Defoliasi yang Berbeda - Alima Maolidea Suri; Maryati Maryati; Jamaludin Jamaludin; Windu Mangiring (Politeknik Negeri Lampung, 2023)
Sunflower seeds are the second largest producer of vegetable oil in the world. Sunflower seeds production ranks third in the world after peanuts and soybeans. Efforts to increase sunflower growth are through cultivation techniques including fertilization with the right dosage and treatment in the form of defoliation. Defoliation aims to increase the intensity of sunlight that can be received by plants, so that it will increase crop yields. Decreasing the intensity of sunlight can reduce yields by 40%. This research was conducted using the experimental method which was arranged in a factorial manner in a Completely Randomized Block Design. The first factor was the Professional NPK dose which consisted of two levels including the recommended dose (P1) and half the suggested dose (P2). The second factor is defoliation time which consists of three levels including phase R1, phase R2, and phase R3. The number of leaves removed is 30% of the number of leaves. The results showed that (1) the half recommended dose of NPK Professional in phase R3 had an effect on the variables of plant height and number of leaves and the recommended dose of Professional NPK had an effect on stem fresh weight; (2) The recommended dose of Professional NPK effects the variables of stem diameter and flower diameter in R2 phase, the recommended dose of Professional NPK affects root dry weight in R2 phase, and the weight of 100 seeds in R1 phase. (3) There is an interaction between the dosage of NPK Professional and defoliation time of sunflower plants. Keywords : Sunflower, NPK, Defoliation